Analysis of Collocational Errors in Selected Iraqi Published Papers - Hussein Dhahi al-Hassnawi (آداب الكوفة, 2017)
The present study attempts to identify and analyse the collocational errors committed in writing by Iraqi EFL researchers whose major is English. The corpus involves (10 ) papers chosen randomly from various Iraqi universities. The research aims at identifying and analyzing both lexical and grammatical collocationalerrors. The results show that the performance of Iraqi researchers in both patterns seems to be influenced by L1 transfer. Moreover, it is found that other factors contribute to the high frequency of collocation errors committed by them, namely the lack knowledge of collocationalskills, especially with regard to collocationalrestriction,the misuse of synonyms, and thetendencyforovergeneralization. Furthermore, it is found that lexical collocation is the most recurrent error throughout the data. This is due to the grammar-based method ,which is broadly adopted in Iraqi classes.